2006
DOI: 10.1080/00222340600773495
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nonlinear Optical Polymers Containing Carbazole and Disperse Red Dye

Abstract: Dye-containing nonlinear optical (NLO) polymers were synthesized: (1) poly(3-(2-(3-(2-isocyanatopropan-2-yl)phenyl)-2-methylpropyl)-4-methyl-1-phenylpyrrolidine-2, 5-dione), P[(DR1,Cz)MSt-PMI], and (2) poly(9-vinyl-9H-carbazole-co-disperse red 1), PAV[DR1-Cz]. The synthesized NLO polymers were characterized by 1 H-NMR, IR, and UV -VIS spectroscopy; differential scanning calorimetry (DSC); and thermogravimetric analysis (TGA). The electro-optic (EO) coefficients (r 33 ) and their NLO properties were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Measurements 1 H NMR spectra were taken on a Varian Gemini-200 FT NMR spectrometer using CDCl 3 and DMSO-d 6 . IR measurements were performed on a Perkin-Elmer Spectrum One FT-IR spectrometer.…”
Section: Isocyanation Preparation Of Poly(vinyl Benzyl Isocyanate) (Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements 1 H NMR spectra were taken on a Varian Gemini-200 FT NMR spectrometer using CDCl 3 and DMSO-d 6 . IR measurements were performed on a Perkin-Elmer Spectrum One FT-IR spectrometer.…”
Section: Isocyanation Preparation Of Poly(vinyl Benzyl Isocyanate) (Hmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, the TMI monomers do not polymerize to any significant extent via free radical bulk homopolymerization, as addressed by Leonie et al 7 The reluctance of TMI monomers to homopolymerize is due to the presence of -methyl group, which causes significant steric hindrance resulting in a substantial reduction of propagation rate coefficient, k p ((60 C, styrene) = 340 L mol À1 s À1 and k p (-methyl styrene) = 2.61 L mol À1 s À1 ). It is concluded that the TMI monomers are not suitable for synthesizing homopolmers or block copolymers.…”
mentioning
confidence: 99%